NEUTRON REFLECTIVITY AND STRUCTURE OF POLYETHER DENDRIMERS AS LANGMUIR FILMS - Saville, P; Reynolds, P; White, J; Hawker, C; Frechet, J; Wooley, K; Penfold, J; Webster, J (1995)
Neutron reflectivity and Π-A isotherm measurements of Langmuir films of polyether dendrimers based on 3,5-dihydroxybenzyl alcohol have elucidated the structure of these interesting molecules at the air-water interface. The neutron reflectivity measurements indicated a collapse of the fourth-generation monodendron, [G-4]-OH, to a bilayer structure. The molecules in the layer next to the water interface were ellipsoidal in structure due to compression and contained a volume fraction of about 25% of the substrate water. The molecules in the layer next to air were spherical with a diameter of 21 Å and contained no water. Isotherm measurements of the monodendron and tridendron series indicated scaling relationships between the area per molecule and the molecular weights of these species. © 1995 American Chemical Society.